The Concept of Environmental Conservation in The Qur’an - M Rizky Herdiansyah; Anggi Taryana; Raka Alifan Rozaqi; Dadan Firdaus (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Environmental degradation caused by human activities has become one of the major issues threatening ecosystem balance and the sustainability of life. In Islam, environmental conservation is considered part of human responsibility as God's vicegerent (khalifah) on earth. The purpose of this study is to examine the concept of environmental protection as presented in Surah Al-A'raf, verse 56 of the Quran, and to evaluate its relevance to current environmental issues. This research employed a qualitative approach using library research. Data were collected from the Qur'an, scholarly journal articles, and other relevant academic literature. The findings reveal that Surah Al-A'raf verse 56 contains a prohibition against causing corruption (fasad) on earth after God has established it in a good and balanced condition. The verse embodies environmental conservation values, including human responsibility toward nature, maintaining ecological balance, and the wise utilization of natural resources. The study also indicates that these values remain relevant to current environmental problems, such as illegal logging, environmental pollution, and excessive exploitation of natural resources. Therefore, Surah Al-A'raf, verse 56, can act as a moral foundation for initiatives aimed at safeguarding the environment and encouraging sustainable progress. These findings offer practical implications for environmental policy and Islamic religious education.